PENGARUH TERAPI BEKAM BASAH TERHADAP TEKANAN DARAH PADA PASIEN DI KLINIK SEHAT DR. ABDURRAHMAN MEDAN TAHUN 2020 - NIA MONICA PUTRI GINTING; EKA AIRLANGGA (JURNAL ILMIAH SIMANTEK, 2021)
Cupping therapy is one of the altenative treatments that is widely used by the public. Wet cupping is believed to havebenefits for treating various diseases and can reduce blood pressure. However, there is also several studies that state thatcupping therapy has no significant effect on blood pressure. Therefore, this statement shall be accompanied by carrying outa research to conclude facts about cupping. To know the effect of wet cupping therapy against blood pressure performed atDr. Abdurrahman Medan Health Clinic in 2020. This type of research is descriptive analytic with cross sectional design bycomparing pre-test and post-test values to one group without comparison. Samples size were 44 people who met theinclusion and exclusion criteria specified in the purposive sampling. Data were analyzed using the T-paired test. Paired-t testresults showed there was an effect of wet cupping therapy against systolic blood pressure with p value = 0.000 (< 0.05) andthere was also an effect of wet cupping against diastolic blood pressure with p value = 0.006 (< 0.05). Cupping therapy candecrease blood pressure.